Mouse Models in Prostate Cancer Translational Research: From Xenograft to PDX - Rea, Domenica (Biomed Res Int, 2016)
Despite the advancement of clinical and preclinical research on PCa, which resulted in the last five years in a decrement of disease incidence by 3-4%, it remains the most frequent cancer in men and the second for mortality rate. Based on this evidence we present a brief dissertation on numerous preclinical models, comparing their advantages and disadvantages; among this we report the PDX mouse models that show greater fidelity to the disease, in terms of histopathologic features of implanted tumor, gene and miRNA expression, and metastatic pattern, well describing all tumor progression stages; this characteristic encourages the translation of preclinical results. These models become particularly useful in meeting the need of new treatments identification that eradicate PCa bone metastases growing, clarifying pathway of angiogenesis, identifying castration-resistant stem-like cells, and studying the antiandrogen therapies. Also of considerable interest are the studies of 3D cell cultures derived from PDX, which have the ability to maintain PDX cell viability with continued native androgen receptor expression, also showing a differential sensitivity to drugs. 3D PDX PCa may represent a diagnostic platform for the rapid assessment of drugs and push personalized medicine. Today the development of preclinical models in vitro and in vivo is necessary in order to obtain increasingly reliable answers before reaching phase III of the drug discovery.